2010
DOI: 10.1073/pnas.0910630107
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q protects Caenorhabditis elegans GABA neurons from calcium-dependent degeneration

Abstract: Mitochondria are key regulators of cell viability and provide essential functions that protect against neurodegenerative disease. To develop a model for mitochondrial-dependent neurodegeneration in Caenorhabditis elegans, we used RNA interference (RNAi) and genetic ablation to knock down expression of enzymes in the Coenzyme Q (CoQ) biosynthetic pathway. CoQ is a required component of the ATP-producing electron transport chain in mitochondria. We found that reduced levels of CoQ result in a progressive uncoord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 64 publications
2
40
0
Order By: Relevance
“…This uncoordinated phenotype emerges during late larval development, progresses in adulthood, and proceeds with a selective cell death pathway activation where apoptotic and mitochondrial fission genes take part, which is a clear signal of initiation of a mitophagy process within these cells as in humans [Rodríguez-Hernández et al, 2009;Cotan et al, 2011]. However, neurons and body muscle cells that use other neurotransmitters, such as dopamine, acetylcholine, serotonin, or glutamate, were more resistant to CoQ depletion [Earls et al, 2010]. Similar phenotypes were described within the same work for knockdown of the genes coq-2 and coq-3.…”
Section: Summarizing the Human Syndrome Of Coq 10 Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…This uncoordinated phenotype emerges during late larval development, progresses in adulthood, and proceeds with a selective cell death pathway activation where apoptotic and mitochondrial fission genes take part, which is a clear signal of initiation of a mitophagy process within these cells as in humans [Rodríguez-Hernández et al, 2009;Cotan et al, 2011]. However, neurons and body muscle cells that use other neurotransmitters, such as dopamine, acetylcholine, serotonin, or glutamate, were more resistant to CoQ depletion [Earls et al, 2010]. Similar phenotypes were described within the same work for knockdown of the genes coq-2 and coq-3.…”
Section: Summarizing the Human Syndrome Of Coq 10 Deficiencymentioning
confidence: 99%
“…First generation of coq-1 mutants are sterile and present both morphological defects and improper development of the organs [Gavilan et al, 2005]. Also, knockdown of coq-1 by feeding bacteria producing RNAi against this gene results in the progressive degeneration of GABA neurons and age-dependent loss of motor coordination [Earls et al, 2010]. This uncoordinated phenotype emerges during late larval development, progresses in adulthood, and proceeds with a selective cell death pathway activation where apoptotic and mitochondrial fission genes take part, which is a clear signal of initiation of a mitophagy process within these cells as in humans [Rodríguez-Hernández et al, 2009;Cotan et al, 2011].…”
Section: Summarizing the Human Syndrome Of Coq 10 Deficiencymentioning
confidence: 99%
“…Mol Syndromol 2014;5:180-186 DOI: 10.1159/000362942 182 than others to CoQ ablation [Earls et al, 2010]. Moreover, the study of Drosophila melanogaster carrying mutations in qless , homolog of PDSS1 , suggested that CoQ promotes the growth of neuroblast lineages, protecting neural cells against mitochondrial stress and apoptosis [Grant et al, 2010].…”
Section: Licitra /Pucciomentioning
confidence: 99%
“…Using C. elegans transgenics that express mutant TDP-43 or FUS or FUS[S57D], referred to herein as mTDP-43 and mFUS respectively) in motor neurons [15] we evaluated the efficacy of these models as drug discovery tools by testing three compounds with known clinically neuroprotective properties: lithium chloride, MB and riluzole [18,19]. The mTDP-43 and mFUS transgenic worms show adult-onset, progressive motility defects leading to paralysis when grown under standard laboratory conditions on solid agar plates over the course of 10 to 12 days [15].…”
Section: Methylene Blue Rescues Mutant Tdp-43 and Fus Behavioral Phenmentioning
confidence: 99%
“…Additionally, the paralysis assay is widely used to study age-dependent degenerative phenotypes and is not observed in wild type non-transgenic worms until they reach advanced age (approximately 20 days) [16][17][18]. Finally, motility defects and adult onset paralysis have been previously observed in worms with degenerating GABAergic motor neurons suggesting that mTDP-43 and mFUS may negatively affect GABAergic neuronal function and survival [19]. …”
mentioning
confidence: 99%